Differences in Pre- and Post-Menstruation Hemoglobin Levels in Students of the Medical Laboratory Technology Study Program at Poltekkes Kemenkes Kupang - Flistiana Lobain; Novian Agni Yudhaswara; Aldiana Astuti (Laboratory Journal of Infectious Diseases, 2025)
Anemia is a common health problem experienced by adolescent girls, especially due to blood loss during menstruation which causes a decrease in hemoglobin (Hb) levels. Hemoglobin is an important protein in red blood cells that functions to transport oxygen from the lungs to all body tissues. Lack of hemoglobin can disrupt body function and potentially cause the risk of ongoing mental complications. This study aims to identify differences in hemoglobin (Hb) levels before (pre) and after (post) menstruation among female students of the Medical Laboratory Technology Study Program at Poltekkes Kemenkes Kupang. The research method used is quantitative with a cross-sectional approach. The sample in this study consisted of 30 female students who were taken using random sampling techniques. Hemoglobin levels were measured twice, namely on the first day of menstruation and after the last day of menstruation, using a POCT (Point of Care Testing) tool that provides fast and practical results. Data analysis was carried out using the Wilcoxon test because the data obtained were not normally distributed. The results of the study showed a significant decrease in hemoglobin levels after menstruation. Before menstruation, the average Hb level was recorded at 12,847 g/dL, while after menstruation it decreased to 11,273 g/dL. The Wilcoxon test results showed a significance value of 0,000 (p < 0,05), which indicated a significant difference between hemoglobin levels before and after menstruation.